Capping Methodology in Cyclodextrin Chemistry: Use of a Symmetrical Diketone Reagent for Regiospecific Installation of Unsymmetrical Imine–Enamine and Imidazole Caps. Issue 9 (2nd February 2014) - Jouffroy, Matthieu; Armspach, Dominique; Louati, Alain; Matt, Dominique; Toupet, Loïc
Abstract Methylated α‐ and β‐cyclodextrin skeletons were both equipped with an unsymmetrical N‐(2‐N‐alkylaminoacenaphthenyl)alkylimine rigid handle. The capping reaction, which consists of condensing a diaminocyclodextrin with highly symmetrical acenaphthenequinone, was found to be regiospecific when starting from cyclodextrin‐diamines without any symmetry element. All modified cyclooligosaccharides have intra‐annular nitrogen donor atoms. They undergo further cyclization on oxidation, whether chemically with 2, 3‐dichloro‐5, 6‐dicyano‐1, 4‐benzoquinone or electrochemically, to give highly strained cyclodextrins capped with an unsymmetrical 1, 2‐disubstituted 1H‐imidazole unit.